A city without care : 300 years of racism, health disparities, and healthcare activism in New Orleans - McQueeney, Kevin (Studies in social medicine., 2023)
"New Orleans is a city that is rich in culture, music, and history. It's also long been a site of some of the most intense racially based medical inequities in the United States. Kevin McQueeney traces that inequity for 300 years of the city's history, beginning at its founding in 1718. McQueeney argues that this racist system emerged as a key component of the slave-based economy in the city, which quickly became institutionalized with the end of Reconstruction and the rise of Jim Crow. He also shows that, despite legislation and court victories in the Civil Rights era, an apartheid health care system still exists today"--